2012
DOI: 10.1002/jso.23037
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of thrombospondin‐1 in stromal myofibroblasts is associated with tumor growth and nodal metastasis in gastric carcinoma

Abstract: This clinical study revealed that overexpression of THBS-1 in stromal myofibroblasts is associated with tumor growth and nodal metastasis in gastric carcinoma. THBS-1 may activate latent transforming growth factor-β1 to stimulate fibroblasts to differentiate into myofibroblasts, though further studies are needed to validate this hypothesis. These results suggest that THBS-1 and myofibroblasts may serve as novel targets for strategies aimed at protection against and treatment of gastric carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 39 publications
2
33
1
Order By: Relevance
“…THBS1 protein was located in tumor cells and was undetectable in stroma. This contrasts with gastric cancer, where THBS1 localized to stroma [62], indicating apparent tissue-specific differences depending on cancer type.…”
Section: Discussionmentioning
confidence: 99%
“…THBS1 protein was located in tumor cells and was undetectable in stroma. This contrasts with gastric cancer, where THBS1 localized to stroma [62], indicating apparent tissue-specific differences depending on cancer type.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, extensive literature presents loss of TSP-1 expression during malignant progression as a hallmark of the ''angiogenic switch'' in a variety of major cancer types [3], with TSP-1 being typically down-regulated under oncogenes activation [4]. Among the hypothetical reasons that could explain high TSP-1 plasma concentrations, some have suggested that TSP-1 may originate from tumor stromal compartment [5]. Nevertheless, one should consider melanoma an exception as melanoma cells also express TSP-1 while their normal counterparts do not [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, further studies are required to confirm these hypotheses. THBS1 has been reported to exert a pro-angiogenic effect in gastric cancer (13)(14)(15)(16)(17), which plays an important role in cancer metastasis. Tumor metastasis is well established as a critical event affecting patient prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have correlated THBS1 expression to tumor angiogenesis, tumor growth and metastasis (8)(9)(10)(11)(12). In gastric cancer, THBS1 may have a pro-angiogenic effect, and elevated THBS1 expression levels have been associated with gastric cancer tumor growth and lymph node metastasis (13)(14)(15)(16)(17). However, thus far, genetic evidence of a role for THBS1 in gastric cancer is lacking.…”
Section: Introductionmentioning
confidence: 99%